EVOLUTION OF DIGITAL PAYMENTS: A COMPARATIVE STUDY OF PRE- AND POST-COVID TRENDS IN HYBRID ENVIRONMENTS - Kumar, Atul; Parab, Tadnya; Shukla, Stuti; Periwal, Chirag; Chourasiya, Sahil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this era of rapid technological advancement, the use of digital payments is booming. It is one of the key measures being promoted by the government under the 'Digital India' campaign to move toward a cashless economy. Digital payments are made through online platforms using electronic media, eliminating the need for physical cash, and enabling people to handle transactions quickly and easily. The government's goal is to create a digitally empowered economy that is faceless, paperless, and cashless. With the rapid growth of internet access and smartphone usage, more people now have the tools to make digital payments. Mobile wallets, apps, and payment platforms have become widely accessible, and digital payments can be made both online and in physical locations. For example, if you buy something from Myntra and pay via UPI, that qualifies as a digital payment. Similarly, if you visit a restaurant and, instead of paying with cash or a card, scan a QR code at the cashier using an app like Google Pay or PhonePe, and complete the transaction through UPI, it is also considered a digital payment since the money is transferred electronically without physical cash. This study investigates whether the importance of digital payments has grown significantly between the pre-COVID and post-COVID periods. A two-sample means test was conducted using survey responses from finance managers at 100 companies in Pune. The findings indicate a notable increase in the importance of digital payments during the COVID-19 period.